Identification of low-order continuos-time models via discrete-time trends of measurements - Janiszowski, Krzysztof B. (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the problem of continuous-time (CT) identification of parameters in transfer functions for low-order linear systems, based on recorded discrete-time (DT) data. Algorithms for direct estimation of CT parameters are developed from rules for transformation of a CT transfer function controlled via a zero-order sampling-and-hold unit into a DT representation.
Keywords: continuous time; transfer function; discrete-time model; identification